The insect crisis : the fall of the tiny empires that run the world - Milman, Oliver (W. W. Norton & Company, 2022)
"A devastating examination of how collapsing insect populations worldwide threaten everything from wild birds to the food on our plate. From ants scurrying under leaf litter to bees able to fly higher than Mount Kilimanjaro, insects are everywhere. Three out of every four of our planet's known animal species are insects. In The Insect Crisis, acclaimed journalist Oliver Milman dives into the torrent of recent evidence that suggests this kaleidoscopic group of creatures is suffering the greatest existential crisis in its remarkable 400-million-year history. What is causing the collapse of the insect world? Why does this alarming decline pose such a threat to us? And what can be done to stem the loss of the miniature empires that hold aloft life as we know it? With urgency and great clarity, Milman explores this hidden emergency, arguing that its consequences could even rival climate change. He joins the scientists tracking the decline of insect populations across the globe, including the soaring mountains of Mexico that host an epic, yet dwindling, migration of monarch butterflies; the verdant countryside of England that has been emptied of insect life; the gargantuan fields of U.S. agriculture that have proved a killing ground for bees; and an offbeat experiment in Denmark that shows there aren't that many bugs splattering into your car windshield these days. These losses not only further tear at the tapestry of life on our degraded planet; they imperil everything we hold dear, from the food on our supermarket shelves to the medicines in our cabinets to the riot of nature that thrills and enlivens us. Even insects we may dread, including the hated cockroach, or the stinging wasp, play crucial ecological roles, and their decline would profoundly shape our own story. By connecting butterfly and bee, moth and beetle from across the globe, the full scope of loss renders a portrait of a crisis that threatens to upend the workings of our collective history. Part warning, part celebration of the incredible variety of insects, The Insect Crisis is a wake-up call for us all."--